2015
DOI: 10.1097/scs.0000000000001335
|View full text |Cite
|
Sign up to set email alerts
|

Oral Propranolol for Parotid Infantile Hemangiomas

Abstract: The aim of our study was to assess the efficacy and safety of oral propranolol for the treatment of parotid infantile hemangiomas. Between October 2009 and January 2013, propranolol was given orally to 30 infants with proliferating hemangiomas at a dose of 1.0 to 1.5 mg/kg per day in our department. The patients included 12 male infants and 18 female infants, aged between 2 and 13 months, with a median of 5.9 months. The lesions were located in the parotid region and measured from 1.5 cm × 2 cm × 0.5 cm to 6 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Furthermore, many studies had suggested that compared with IHs at other sites, parotid hemangiomas are more resistant to systemic medications, including propranolol, 7,21,22 with a higher possibility of relapse 4 and surgical correction after regression 2 . However, some other studies indicated that the outcome of propranolol treatment in parotid hemangiomas is comparable to or even better than that of IHs at other sites 9,23,24 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many studies had suggested that compared with IHs at other sites, parotid hemangiomas are more resistant to systemic medications, including propranolol, 7,21,22 with a higher possibility of relapse 4 and surgical correction after regression 2 . However, some other studies indicated that the outcome of propranolol treatment in parotid hemangiomas is comparable to or even better than that of IHs at other sites 9,23,24 …”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported the effectiveness of propranolol in hemangioma of the parotid gland. 7,8 However, Harris and Phillips found that parotid hemangiomas have a lower response rate to propranolol and need a longer treatment course compared to infantile hemangioma at other sites. 9 Most infantile hemangiomas complete their proliferative growth phase before 9 months of age.…”
Section: Abbreviationmentioning
confidence: 99%